Foliar fertilization of phosphorus with it’s different doses; for the performance of the cultivation of frijol castilla (Vigna unguiculata L.) in the province of Barranca - Cruz Nieto, Dante Daniel (2019)
This research is based on the fertilization of phosphorus in the cultivation of Castilianbeans in the Province of Barranca, the appropriate dose was determined to obtain ahigher yield. For this the experiment was carried out in the Fundo Los Anitos, this wasapplied in three moments and its treatments are: T1 = 0, T2 = 0.5, T3 = 1,0 and T4= 1,5 liters per 200 l. of water. The block design was used completely at random, thestatistical operation that was used was the analysis of variance and the Duncan test.Obtained the results of the evaluations, it was determined that the T4 reached thehighest yield with 2,9 Tm / ha., The other evaluations in the field obtained good resultswith higher doses, these are: plant height, number of flowers per plant, sampling ofpods and weight per plant, all being statistically homogeneous. Regarding the dataobtained in the laboratory as length of pod, number of grains, weight of 100 seeds,did not show significant differences, the data of leaf analysis stood out the T4 with0,72 g of phosphorus/100 of dry matter and cost benefit S/ 0,53 Nuevo Soles